Determination of dopamine, noradrenaline, and adrenaline in Krebs–Henseleit solution by liquid chromatography coupled with tandem mass spectrometry and measurement of their basal release from Chelonoidis carbonaria aortae in vitro. (13th September 2020) - Britto‐Júnior, José; Antunes, Natalícia J.; Campos, Rafael; Sucupira, Mauro; Mendes, Gustavo Duarte; Fernandes, Fernanda; Moraes, Manoel Odorico; Moraes, Maria Elisabete A.; De Nucci, Gilberto
Abstract: This study presented for the first time the development and validation of a sensitive method for quantification of dopamine, noradrenaline, and adrenaline in Krebs–Henseleit solution by LC–tandem mass spectrometry. Aliquots of 2.0 mL calibrators, quality controls, and samples of Krebs–Henseleit solution incubated with tortoise's aortic ring for 30 min were extracted by solid‐phase extraction. Catecholamine separation was achieved on a 100 × 4.6 mm LiChrospher RP‐8 column and the quantification was performed by a mass spectrometer equipped with an electrospray interface operating in positive ion mode. The run time was 4 min and the calibration curve was linear over the range of 0.1–20.0 ng/mL. The method was applied to the measurement of basal release of dopamine, noradrenaline, and adrenaline from the tortoise Chelonoidis carbonaria aortae in vitro. One aortic ring (30 mm) per tortoise ( n = 5) was incubated for 30 min in a 5 mL organ bath filled with Krebs–Henseleit solution. The method demonstrated sensitivity, precision, and accuracy enough for its application in the measurement of basal release of these catecholamines from C. carbonaria aortic rings in vitro. The mean (standard deviation) concentrations of dopamine, noradrenaline, and adrenaline were 3.48 (2.55) ng/mL, 1.40 (0.57) ng/mL, and 1.87 (1.09) ng/mL, respectively.